Category Membership as a Criterion to Evaluate the Soundness of Analogical Inferences - Minervino, Ricardo Adrian (2023)
The standard approach to analogical reasoning posits that the mechanism that people employ to ensure the soundness of analogical inferences consists in copying unmapped individual explicit base relations, substituting corresponding source entities with target entities, and generating slots for base entities that were unmapped. Alternatively, we contend that when the gist of the information to be transferred is better captured by relational categories than by explicit individual relations, people resort to searching for target exemplars of the base relational categories, disregarding similarity between relations. Experiment 1 revealed that for this kind of analogy, inferences that did not resemble the base analog in terms of explicit individual relations but were built on exemplars of the base relational category were judged as sounder than inferences that matched the base analog in terms of relations but not in terms of a common category. Within the framework of the proposed approach, we postulated that inference evaluation also depends on the similarity between the base and target exemplars on relevant aspects. Experiment 2 revealed that inferences were judged as sounder when the exemplars upon which the inferences were built matched the base exemplars along salient dimensions of the relational category they shared. The cognitive mechanisms unveiled by the current results suggest new avenues along which current theorization and modeling of analogical inference may develop.